Reverse *-Centralizers on *-Lie Ideals - Altay, A (Iraqi Journal of Science, 2024)
The purpose of this paper is to prove the following result : Let R be a 2-torsion free prime *-ring , U a square closed *-Lie ideal, and let T: RR be an additive mapping. Suppose that 3T(xyx) = T(x) y*x* + x*T(y)x* + x*y*T(x) and x*T(xy+yx)x* = x*T(y)x*2 + x*2T(y)x* holds for all pairs x, y  U , and T(u) U, for all uU, then T is a reverse *-centralizer.